Antibiotic stewardship program (ASP) implementation is more effective than the national action plan for rational drug use - Karaali, Cem; Esin, Huseyin; Ureyen, Orhan; Namdaroglu, Ozan Barıs; Kale, Murat Can; Emiroglu, Mustafa; Yakan, Savas; Ilhan, Enver; Oztop, Mehmet Burak; Kose, Sukran (The Journal of Infection in Developing Countries, 2025)
Introduction: In this study, we investigated the long-term effects of different antibiotic stewardship programs on surgical prophylaxis (SP) and the continuation of SP at discharge prescription in two general surgery clinics. Methods: We retrospectively examined SP practices in the general surgery clinics of two hospitals. In Clinic A, a modified antibiotic stewardship program (mASP) was implemented, while in Clinic B, practices were conducted within the scope of the National Action Plan for Rational Drug Use (NAPRDU). A cross-sectional comparison was made by including quarterly data from both clinics for the years 2013, 2016, 2018, and 2023. Results: When the SP practices in clinics A and B were analyzed in detail according to year, we found that SP indication, SP use for > 24 hours, antibiotic use in prescription, and all stages of SP (prescription and non-prescription) improved for both clinics except for the time of SP administration (p < 0.05). Moreover, a significantly greater and faster improvement in these parameters was found in clinic A than in clinic B. Conclusions: Our study showed that the mASP and the NAPRDU have positive long-term effects on SP practices in general surgery clinics and the implementation of SP in discharge prescriptions. However, in clinics where mASP was applied, SP practices generally improved faster and more effectively, especially in terms of the antibiotics prescribed in discharge.